CRITICISING STATELESSNESS STATUS AND ASEAN’S ROLE TOWARDS ROHINGYA ATROCITIES - Naeli Fitria (Universitas Potensi Utama, 2020)
Rohingya statelessness is increasingly recognized as a serious, worldwide human rights violations concern. The rejection of Rohingya ethnic group by Myanmar Government has resulted in life-threatening circumstances. International protocol, such as, the 1954 Convention relating to the Status of Stateless Persons, as a tool in giving shelter for stateless people are still weak in the implementation. Major drawback in providing shelter for Rohingya refugees which have been implemented by Bangladesh Government, however, has inseparable factor in upholding human rights for refugees. To date, ASEAN has poor human rights mechanism in addressing human rights violations issue within the region. The avoidance taken by ASEAN reflected the concept of negligence. Thus, this paper sought to examine the factors of Citizenship and ASEAN’s Negligence in addressing Rohingya issue.